Covid-19 : analysis on financial wellbeing during the implementation of Movement Control Order in Malaysia - Siti Nurul Munawwarah Roslan,; Kastury Gohain,; Dayangku Azriani Awang Ismail,; Vikniswari Vija Kumaran,; Mohd Khairi Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The Malaysian people’s well-being has suffered as a result of COVID-19 pandemic. The welfare of Malaysians has also been impacted by the pandemic, as the Malaysian government has decided to implement Movement Control Orders (MCO) to prevent the virus from spreading throughout the country. Many Malaysian households’ financial well-being has suffered as well due to the crisis consequences. Therefore, this study concentrated on the subjective financial well-being analysis of Malaysians during the implementation of the Movement Control Order (MCO). This is a quantitative study with 293 respondents, 163 of whom were from the B40 group and 130 from the M40 group. The descriptive analysis and Structure Equation Modelling (SEM) technique were used in the data analysis (SEM). The study found that the impact of expenses on financial well-being is greater in the “B40 income group” than in the “M40 income group.” To support the financial well-being of B40 and M40 income groups, the government should implement an effective targeted policies, programmes, and incentives. Following the implementation of MCO in Malaysia, future research should focus on Malaysian households’ financial well-being aspect.